Interpersonal Conflict Resolution Among Students in Multicultural Schools: An Interpretive Study Grounded in the Local Value of Songu Lara Mombangu - Rani Radhiyallah; Bau Ratu; Nurwahyuni; Azam Arifyadi; Misnah; Mohamad Awal Lakadjo (EMPATI: Jurnal Bimbingan dan Konseling, 2026)
Abstract. Amidst growing cultural diversity in Indonesian schools, this study investigates interpersonal conflict among students in multicultural secondary schools and explores how the local value Songu Lara Mombangu informs school-based conflict mediation. Using a qualitative multiple-case study design, data were collected through in-depth interviews, participant observation, and document analysis in three culturally diverse schools in Central Sulawesi. Findings reveal that conflict often arises not from ethnic identity, but from miscommunication, divergent social norms, and peer dynamics. Although students’ awareness of Songu Lara Mombangu is limited, its values are reflected in daily practices of cooperation and relational repair. The study underscores the importance of culturally responsive counseling grounded in local wisdom. It contributes to expanding theories of social identity and intersectionality by offering a contextualized lens for conflict resolution. These insights support the development of inclusive educational policies and training programs that align with students’ cultural realities.